2009
DOI: 10.4088/jcp.08m04666yel
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized Study of Minocycline for the Treatment of Negative and Cognitive Symptoms in Early-Phase Schizophrenia

Abstract: clinicaltrials.gov Identifier: NCT00733057.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
280
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(301 citation statements)
references
References 114 publications
(118 reference statements)
13
280
2
6
Order By: Relevance
“…Since minocycline had no effect on the TNFR2 expression levels in the NPCs derived from the hippocampi of NaCl offspring per se, we propose that the mode of action of minocycline is promoted through the regulation of microglial derived TNF-α and IL-1β. In human patients minocycline had beneficial effects at a similar dosage as we have used in our study (Levkovitz et al, 2010). In a recent in vitro study it was shown that minocycline inhibited the production of TNF-α from IFN-γ-activated microglia (Seki et al 2013).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Since minocycline had no effect on the TNFR2 expression levels in the NPCs derived from the hippocampi of NaCl offspring per se, we propose that the mode of action of minocycline is promoted through the regulation of microglial derived TNF-α and IL-1β. In human patients minocycline had beneficial effects at a similar dosage as we have used in our study (Levkovitz et al, 2010). In a recent in vitro study it was shown that minocycline inhibited the production of TNF-α from IFN-γ-activated microglia (Seki et al 2013).…”
mentioning
confidence: 54%
“…With an average of 5ml water intake per 250g rat per day, the animals received an average daily dosage of 3mg/kg over the course of approximately 70 days. The daily dosage was adapted from treatments in schizophrenic patients (Levkovitz et al, 2010). Water bottles were changed every second day to ensure minocycline stability.…”
Section: Minocycline Treatmentmentioning
confidence: 99%
“…In cuprizone-fed C57BL/6 mice, minocycline reduced microglial activation and demyelination in the brain and prevented disturbances in motor coordination (Pasquini et al, 2007;Skripuletz et al, 2010;Tanaka et al, 2013). Furthermore, minocycline in combination with an antipsychotic such as risperidone, olanzapine, quetiapine, or clozapine significantly improved positive, negative, and cognitive symptoms in recent-onset or chronic schizophrenia patients (Levkovitz et al, 2010;Ghanizadeh et al, 2014;Chaves et al, 2015;Kelly et al, 2015). From these results, it is likely that application of minocycline can dampen M1 signaling, subsequently resulting in skewing of M2a microglia that reduce proinflammatory signaling and increase production of anti-inflammatory cytokines.…”
Section: Pharmacological Approach To Neuroinflammation In Asd and Schmentioning
confidence: 96%
“…Therefore, our study provides insight into why immune-and glutamate-modulating therapies may be helpful for acutely ill suicidal patients suffering from depression. Potential candidate drugs include the tetracycline antibiotic minocycline, which inhibits microglial activation by blocking NF-kappa B nuclear translocation [39][40][41][42] or antiinflammatory inhibitors of cyclooxygenase-2 [43,44]. Furthermore, severely depressed suicidal patients may Figure 3 Illustration of QUIN-immunopositive cell densities.…”
Section: Discussionmentioning
confidence: 99%